EFFECTS OF OUTSOURCING DECISION ON ORGANISATION PERFORMANCE IN THE MANUFACTURING INDUSTRY CASE OF UNILEVER GROUP LIMITED IN INDIA - Bansal, Ankurita; Kavita (International Journal of Psychosocial Rehabilitation, 2021)
Firms have always sought ways to gain a competitive advantage over their competitors; one avenue that firms have pursued to improve their competitive position in this new business environment has been to increase the role of outsourcing in their operations, which has been found to provide a competitive advantage and heightened performance to these firms. The study therefore was purposed to establish the effect of outsourcing decisions on the organizational performance of the manufacturing industry, using India Unilever Group Limited as a case study. Information technology adoption, cost reduction and top management support and commitment were positively correlated to organization performance The study recommends that the management should take into account the variables considered since the results show that there is a significant relationship between the predictors of information technology adoption, top management support and commitment, focus on core competencies and cost reduction (taken together), and organization performance in Indian manufacturing firms.